Diagnosis of student subsunctors about biological evolution: The conceptual map as a research tool - De Souza, Mariana Carvalho; dos Santos, Solange Xavier [UNESP] (Fronteiras: Journal of Social, Technological and Environmental Science, 2020)
The Biological Evolution (BE) represents a unifying theory of all areas of Biological Sciences. But this teaching is a concern not only in Brazil, but also in the world, due to conflicts with mistaken ideas and concepts, cognitively rooted in students. Aiming to develop subsidies to facilitate teaching and learning about BE, based on the Theory of Meaningful Learning, this work aimed to carry out a survey of subsunctions related to the knowledge of EB among high school students, usingf Conceptual Maps (CM) as a research tool. So, we offer to students a workshop about the basics for building CM, culminating in the building, by each participant, of their own CM related to EB. An analysis of these MC allowed to identify deficiencies in the understanding of evolutionary concepts, in addition a simplistic and lamarckist vision of BE. Thus, it appears that the MC, used as a tool to research, allows students to express themselves freely, revealing the cognitive aspects of the learning process about BE.
Diagnóstico dos Subsunçores dos Estudantes sobre Evolução Biológica: O Mapa Conceitual como Ferramenta de Investigação
Keywords: Active Methodologies; Challenges in Teaching Biological Evolution; High School; Meaningful Learning